The Role of the Academia in Curbing Insecurity in Nigeria: A Study of Niger State Polytechnic, Zungeru - Ishaq Abubakar; Saudia Elsauud Sulaiman; Abdullahi Aliyu (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
The major aim of this study was to explore the role of high level of education in Niger State Polytechnic, Zungeru in mitigating insecurity menace in Nigeria. A total of 239 sample made up of Part Time and Regular Students responded to a closed-ended structured questionnaire designed for the study. Two research questions and two hypotheses were formulated to guide the study. Means and standard deviations were calculated to answer the research questions and Kendal’s Tau-B (T b) Correlation was used for testing the hypotheses. Major findings revealed factors that constitute high level of education and its challenges that may affect the role of the academia in curbing insecurity to include lack of proper understanding of local and international dimensions of security; prevention of people from being recruited into banditry and insurgency; and inability of the academia to steer society away from poverty, unemployment, disease and violence. Also revealed are inherent challenges in the academia to include unsecured environment, cultism and gangsterism, dwindling level of nationalism and patriotism, lack of national cohesion, non implementation of research findings and overcrowded classes in era of global pandemic like COVID 19 where physical distancing is a social requirement. Based on the findings, it was recommended that government should invest heavily in ICT infrastructures of the academia to enhance technological innovations for curbing security threats as well as ensure effective implementation of research findings from the academia.